Applicability of newly developed PET/bio-based polyester blends for hot-filling bottle. (December 2021) - Shin, Hojun; Park, Sangyoon; Thanakkasaranee, Sarinthip; Sadeghi, Kambiz; Lee, Youngsoo; Tak, Guman; Seo, Jongchul
Highlights: Industrial method of bottle production called injection stretch blow molding is used. PEICT biobased polyester is blended to homo-PET for heat resistant bottle. PEICT improved Tg and the thermal shape stability of PET bottle during hot-filling. Heat resistant bottle was prepared through a short and simple production method. Novel heat resistant PET/PEICT bottle is manufactured for use in beverage industry. Abstract: ECOZEN®T110 (EZT), as a bio-based polyester has been used to improve the glass transition temperature (Tg ) and thermal shape stability of polyethylene terephthalate (PET). In this study, the applicability of PET/EZT blends for manufacturing hot-filling bottles using an injection stretch blow molding machine in a conventional process was evaluated. A fully miscible blend (single Tg ) was observed in 10 % EZT, despite the homogeneous phase being maintained in all other EZT ratios (30 %, 50 %, and 70 %). The addition of EZT led to an increase in the Tg and the transparency of the bottles, and maintains their original shape after the hot-filling tests. High Tg bottles with a low melting point and crystallinity were obtained, circumventing the need for complex equipment and time-consuming processes that are otherwise required for conventional PET bottles. Therefore, the PET/EZT blends can be used as an alternative material to manufacture hot-filling bottles using conventional bottle processing.